Respostas de equivalência em idosos com deterioração cognitiva - BASTOS, Natália de Nazaré Albuquerque (Universidade Federal do Pará, 2019)
Alzheimer’s disease is a degenerative process typical of elderly populations and that affect a variety of neuronal structures, with focal lesions in the hippocampal area that are strongly related to associative learning and memory. Although various studies focusing on Alzheimer have been reported, none of them has focused on equivalence-type responding after the observation of stimulus pairs of the AB, AC type (Leader et al., 1996). Accordingly, the present study consisted of a replication of the experiments by Leader et al. (1996) on pairing-based equivalence in groups of elderly institutionalized people with and without Alzheimer. The results showed that none of the groups performed above chance. Thus, two novel groups were included in the study: one with young subjects, and another with people in their fifties. Globally we observed that more than institutionalization of demencia, age was the main factor behind our participants’ response scores: young participants performed at a higher level than the other groups.